Analysis of Development Policy Based on Economic Activities of the Rupat Island Community - Muslim Muslim; Ari Nurwahidah; Muklis Muklis; M. Rachmadi Rachmadi (Jurnal Mamangan, 2024)
For years, the residents of Rupat Island have been involved in economic activities in Malaysia. The border area has undergone many changes in recent years, especially in the Rupat Island region. This study aims to analyze policies based on the economic activities of the community on Rupat Island. The research method used is qualitative descriptive method. Data was collected through in-depth interviews with key informants, and secondary data was obtained from documentation held by Unit Pengelola Pelabuhan (Port Operator). Research findings indicate that the commodities produced by the people of Rupat Island are mostly sold to neighboring Malaysia, particularly fresh fish catches from the sea. This occurs due to the relatively high selling price compared to the prices in Dumai or its surrounding areas. In addition to marine products sold to Malaysia, rubber from plantations has also become a commodity exported to the neighboring country. The community engages in this practice with the hope of achieving a higher selling price than if they were to sell in the local market. The people of Rupat Island are currently consuming many Indonesian products, especially staple food items, to meet their basic needs. This is different from before the improvement of road infrastructure and the operation of the roll-on/roll-off (RoRo) passenger and cargo ferries that began in 2011. Sustainable development policies and programs are needed so that the community can feel the impact of development and empowerment. The development of roads and bridges, the enhancement of economic growth in the primary and secondary sectors, as well as the provision and management of transportation infrastructure and facilities, aim to improve accessibility and the quality of regional infrastructure to facilitate the smooth flow of economic activities for the community.